Rancang Bangun Vertical Wind Axis Turbin (VWAT) Dua Tingkat - Jefri Lianda; Zulkifli Zulkifli (UIN Sultan Syarif Kasim Riau, 2016)
This paper focuses on improving the performance of vertical axis wind turbines (VWAT)to generate electricity through a permanent magnet generator. One method possible use is theselection of the number and angle Savonius windmill. Savonius turbines are known to have lowefficiency, but the construction is cheap and simple, and can receive wind from any directionand high starting torque. The focus of this study is to test the performance of a wind turbineSavonius 2 levels . This research resulted in a windmill with 59 watts of power . Average voltageis generated in the form of 3 -phase AC voltage of 6,57 volt AC to 18,61 volt AC , and thenstored into the battery using the battery charger.Keywords: permanent magnet generator, savonius, VWAT